MALAYSIAN ESL LEARNERS’ EXPERIENCES WITH AI-DRIVEN VOICE PRACTICE USING CHATGPT AND TRADITIONAL ROLE-PLAY - Tan , Wei Xing; Ismail, Hanita Hanim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Artificial intelligence (AI) speaking tools are increasingly used in language education to provide ESL learners with flexible and low-pressure opportunities for oral practice, whereas peer-based activities such as role-play offer authentic communicative experiences that develop interactional and social skills. Despite these opportunities, many learners continue to face challenges in developing speaking proficiency due to limited practice, anxiety during interactions, and inconsistent feedback, which can hinder overall communicative competence. Therefore, this qualitative study explores ESL learners’ experiences with ChatGPT voice conversations alongside peer role-play, focusing on engagement, emotional comfort, confidence, and challenges encountered during speaking practice. Six ESL learners from a Malaysian polytechnic participated through semi-structured interviews, prolonged observations, and reflective journals. The findings reveal that learners perceived ChatGPT as a safe and non-judgmental environment that reduced anxiety and encouraged more frequent speaking, while peer role-play, though sometimes intimidating, offered richer interaction through facial expressions, tone, and spontaneous communication. Additionally, practising with ChatGPT enhanced learners’ confidence and prepared them for peer sessions, whereas peer interaction increased motivation through collaboration and shared support. Nonetheless, challenges such as accent recognition issues, repetitive responses, and occasional technical disruptions limited the effectiveness of AI-based practice. Overall, the study suggests that combining ChatGPT with peer-based activities provides a balanced approach for developing ESL speaking proficiency, leveraging both technological support and meaningful human interaction.